Delayed Facial Palsy:Uncommon Complications ofMicrovascular Decompressionfor Hemifacial Spasm - Faris Khairuddin Syah; Ervina Hutabarat (Magna Neurologica, 2023)
Background: Microvascular Decompression (MVD) is considered the most effective treatment for reducing hemifacial spasm (HFS) and achieving long-term resolution. However, in rare cases, this procedure can lead to delayed facial palsy, characterized by facial weakness occurring more than 24 hours after surgery. Case: A 50-year-old woman complaining of twitching in the right face, from the eye corner to the eyebrows and mouth, for 2 years. The Brain MRI-FIESTA revealed a neurovascular attachment between the right facial nerve and the right posterior inferior cerebellar artery. Despite medical treatment, the patient experienced dissatisfaction due to incomplete symptom remission and drowsiness from drug side effects. After undergoing MVD, the twitches disappeared. However, twelve days later, the patient developed right facial weakness, and after three months of rehabilitation, it was resolved. Discussion: HFS is a rare condition characterized by involuntary facial twitches that can significantly disrupt daily activities, despite being painless. Proper management can be provided according to the needs of the patient and the choices of HFS management include medications, botulinum toxin injection, and MVD. The potential side effects of each procedure should be carefully considered when making treatment decisions. It is crucial to thoroughly evaluate and monitor post-surgical conditions. Conclusion: Delayed facial weakness may be attributed to gradual edema occurring after surgery. The use of Teflon to separate nerve tissue and blood vessels, although beneficial, can sometimes be perceived as a foreign body leading to inflammation. Facial weakness can be managed with facial muscle exercises without requiring special treatment.